A novel approach to the analysis of thermal response test (TRT) with interrupted power input - Luo, Jin; Zhang, Yuhao; Tuo, Jiasheng; Xue, Wei; Rohn, Joachim; Baumgärtel, Sebastian (Energies, 2020)
The quality of measuring datasets of the thermal response test (TRT) significantly influences the interpretation of borehole thermal parameters (BTP). A thermal response test with an unstable power input may induce an unacceptable error in the estimation of the borehole thermal parameters. This paper proposes a novel approach to treat the dataset with interrupted power input. In this approach, the test records were segmented into several subsections with a constant time interval of 100 min, 60 min, and 30 min, separately. The quality of each data section was assessed and analyzed. Then, two algorithms, including the continuous algorithm and semi-superposition algorithm, were developed. The results estimated by the linear source model (LSM) were compared with one Thermal response test datasets with a stable power input at the same testing site. It shows that the effects of power interruption during the test can be effectively mitigated by deploying both the continuous and semi-superposition methods. The lowest deviation of the calculated thermal conductivity to a thermal response test with stable power input was 2.8% in the continuous method and 0.9% using the semi-superposition method. Thus, the proposed approaches are effective measures to mitigate the effects of interrupted power input on the interpretation of the thermal properties of the ground.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Borehole thermal parameters; Interrupted power input; Measuring outputs; Thermal response test (TRT)

Calculating energy and its spatial distribution for a subsurface urban heat island using a GIS-approach - Schweighofer, Julian; Wehrl, Michael; Baumgärtel, Sebastian; Rohn, Joachim (Geosciences, 2021)
In urban areas, the human influence on the city-ecosystem often results in a Subsurface Urban Heat Island (SUHI), which can be used geothermally. Unfortunately, a model of a SUHI does not consider the geology and hydrogeology of the subsoil. These can vary significantly over short distances, and are of considerable importance for the energy balance. In this work, we calculated the energy and its density stored in the subsoil via a SUHI. For this so-called energy-SUHI (e-SUHI), we evaluated the geology and its physical parameters for the first 20 m below ground level in the German city of Nuremberg and linked them to measured underground temperatures in a GIS application. This approach revealed stored energy of 1.634 × 1010 MJ within the soil and water for the study area with an area of 163 km2 and a volume of 3.26 × 109 m3. It corresponds to an average energy density of 5.0 MJ/m3. The highest energy density of 16.5 MJ/m3 was found in the city center area and correlated well to increases in subsurface temperature. As expected, our model reacts sensitively to thickness changes in the geological layers and the unsaturated zone.
CRIS-Team Scopus Importer:2021-01-29
Keywords: Energy-SUHI; Geothermal energy; GIS; Subsurface Urban Heat Island (SUHI)

Detecting Groundwater Temperature Shifts of a Subsurface Urban Heat Island in SE Germany - Schweighofer, Julian; Wehrl, Michael; Baumgärtel, Sebastian; Rohn, Joachim (Water, 2021)
The subsurface beneath cities commonly shows a temperature anomaly, a so-called Subsurface Urban Heat Island (SUHI), due to anthropogenic heat input. This excess heat has multiple effects on groundwater and energy resources, such as groundwater chemistry or the efficiency of geothermal systems, which makes it necessary to investigate the temporal development of a SUHI. For this purpose, temperature profiles of 38 observation wells in the German city of Nuremberg were evaluated from 2015 to 2020 and the measured temperature changes were linked to the surface sealing. The results show that the groundwater temperatures changed between -0.02 K/a and +0.21 K/a, on average by +0.07 K/a during this period. A dependence between the temperature increase and the degree of sealing of the land surface was also observed. In areas with low surface sealing of up to 30% the warming amounts were 0.03 K/a on average, whereas in areas with high sealing of over 60% significantly higher temperature increases of 0.08 K/a on average were found. The results clearly emphasize that the subsurface urban heat island in its current state does not represent a completed process, but that more heat energy continues to enter the subsoil within the city than is the case with near-natural land surfaces.
CRIS-Team WoS Importer:2021-06-04

Experimental study of road deicing by using the urban groundwater under the climatic condition of Nuremberg city, Germany - Baumgärtel, Sebastian; Rohn, Joachim; Luo, Jin (SN Applied Sciences, 2020)
Traffic accidents caused by heavy icing and snowing kept increasing in Germany in recent years, and many deicing methods were therefore developed. These methods either harm the environment (deicing salt) or damage roads (snowplows). As an alternative, the heating of roads using electricity or heated water has been proposed. This study considers the direct use of groundwater for road deicing in urban centers. The climatic and hydrological setting of Nuremberg city is referenced for a testing setup inside a cooling chamber using concrete slabs to test inlet water temperatures under different ambient temperatures. They were designed with 100 mm and 200 mm coil distance and both with an installation depth of around 40 mm. Additionally, an outside test field in a similar fashion is built to validate the measurements inside a chamber. The experiments indicated that a groundwater temperature of 10 degrees C is sufficient to keep the surface ice-free in typical winter days in the study area. Furthermore, the snow did not accumulate on the outside test field during snowfall events. The usability of this heating method could, therefore, be recommended for road deicing under such climatic condition.
CRIS-Team WoS Importer:2020-06-16

The performance of geothermal passive heating and cooling for asphalt and concrete pavement - Baumgärtel, Sebastian; Schweighofer, Julian; Rohn, Joachim; Luo, Jin (Developments in the Built Environment, 2021)
Hydronic pavement heating and cooling applications have been well established to provide road safety over the past two decades. However, most of the systems run on asphalt, only a few are tested with concrete, and there rarely is a comparison between those two common materials in their heating and cooling performance. In this work, a field study was carried out using asphalt and concrete as pavement material for pavement heating and cooling under the climatic conditions of the city Erlangen, Germany. Both heating performance in winter and cooling performance in summer were tested with similar setups and a low inlet temperature of 10 degrees C. The results indicate that asphalt's heating performance is worse than that of concrete, showing slightly lower surface temperatures and limited snow melting capabilities. During heavy snowfall, concrete's surface remained snow-free, while asphalt's surface was covered under a thin layer of snow, indicating that snow is melted not fast enough. However, in summer, asphalt, due to its lower albedo, had a significantly higher energy output of 450 W/m(2) compared to 290 W/m(2) of concrete. Therefore, asphalt showed good cooling perfomance, compared to concrete. Thus, it is concluded that both materials have advantages and disadvantages in geothermal passive heating and cooling, which leave the decision on appropriate material to match the specific planned parameters and environmental requirements.
CRIS-Team WoS Importer:2021-08-13